Identification of Tyrosinase from Dioscorea alata Tuber Extract by Homology Driven Proteomics Approach - Samy Balakrishnan, Gopal; Kalirajan, Jegatheesan (Current Proteomics, 2016)
Tyrosinase a copper-containing metalloprotein that catalyzes the oxidation of tyrosine in particular L-DOPA to L-Dopaquinone, which produces brown pigments in the wounded tissues. The industrial demand for tyrosinase enzyme is increasing as it has a wide range of applications in the field of food, pulp, paper, textile industry, medicine and in environmental technology. In the present investigation, tyrosinase was extracted from Dioscorea alata, a plant source. The enzyme activity of acetone precipitated protein was determined to be 10.6 mkat/ml and the isolated protein depicted the molecular weight of around 40 kDa. The isolated enzyme was confirmed to be tyrosinase using zymogram with 3, 4 dihydroxy- L-phenylalanine as substrate. The tyrosinase from SDS-PAGE band was eluted and precipitated by freeze drying. The precipitated enzyme was then solubilized and the optimum pH and temperature values for maximum enzyme activity were found to be 6.7 and 25°C respectively. Kinetic studies were carried out under optimal conditions and the Km and Vmax value were found to be 7.14 mM and 0.1 s-1 respectively. The crystallized enzyme was separated by SDS-PAGE and the gel was digested by in-gel in solution technique for LC-MS for characterization of enzyme. The enzyme sequence from the LC-MS spectrogram was identified by Homology driven proteomics approach. Though a group of analogous sequences have been found from other organisms, the lack of sequence data in protein databases leads to find a match in D. alata itself. But the Molecular characterization confirmed that the protein isolated from D. alata was tyrosinase.
Keywords: michaelis menten kinetics